Dissolution kinetic mechanisms of FeCr₂O₄ spinel in MgO-Al₂O₃-SiO₂ slag system: Elemental dissolution and component diffusion - Shao, Kang; Chen, Zhang; Wang, Lijun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
The molten chromite reduction direct alloying process serves as a pivotal metallurgical technology in stainless steel production, offering advantages such as reduced carbon consumption and improved production efficiency. In this study, to reveal the dissolution mechanism of chromite, pure phase of synthetic FeCr2O4, the main component of chromite, was used to replace chromite with complex compositions. The dissolution kinetics of FeCr2O4 in MgO-Al2O3-SiO2 slag were systematically investigated as functions of stirring intensity, MgO/ SiO2, and temperature, revealing its non-isothermal reactive dissolution characteristics. Experimental results demonstrated that the solubility of Cr2O3 exhibited a trend of initial increase followed by subsequent decrease as the MgO/SiO2 mass ratio increased. The maximum solubility was observed at a MgO/SiO2 mass ratio of 0.56. Additionally, temperature-related studies indicated that the dissolution of FeCr2O4 is progressively enhanced with increasing temperature under elevated thermal conditions (1500-1600 ℃). Meanwhile, scanning electron microscopy (SEM) analyses confirmed that the interfacial reaction between FeCr2O4 and slag components generated MgAl2O4, MgCr2O4 and MgO-xFeO solid solution, forming a boundary layer on the surface of unreacted FeCr2O4.The dissolution reaction on the surface of FeCr2O4 was the rate-controlling step in the dissolution process. The calculated activation energy of the dissolution process was 65.43 kJ·mol-1.
Keywords: slag; dissolution; MgO/ SiO2; interface; dissolution kinetics